2010
DOI: 10.1002/bit.23018
|View full text |Cite
|
Sign up to set email alerts
|

Processing/structure/property relationship of multi‐scaled PCL and PCL–HA composite scaffolds prepared via gas foaming and NaCl reverse templating

Abstract: In this study, we investigated the processing/structure/property relationship of multi-scaled porous biodegradable scaffolds prepared by combining the gas foaming and NaCl reverse templating techniques. Poly(ε-caprolactone) (PCL), hydroxyapatite (HA) nano-particles and NaCl micro-particles were melt-mixed by selecting different compositions and subsequently gas foamed by a pressure-quench method. The NaCl micro-particles were finally removed from the foamed systems in order to allow for the achievement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 30 publications
2
53
0
Order By: Relevance
“…For example, Shor et al [20] Previous studies also showed that the addition of HA to PCL does not result in a significant increase in cell numbers. This was structure independent as this observation was made for foams [38], films [39] and surface coatings [40]. The composition has indirect effects such as changes in the localization of the cells due to differences in surface properties.…”
Section: Discussionmentioning
confidence: 72%
“…For example, Shor et al [20] Previous studies also showed that the addition of HA to PCL does not result in a significant increase in cell numbers. This was structure independent as this observation was made for foams [38], films [39] and surface coatings [40]. The composition has indirect effects such as changes in the localization of the cells due to differences in surface properties.…”
Section: Discussionmentioning
confidence: 72%
“…The biocompatibility of PLA scaffolds was investigated in vitro by using MG63 cells, as these cells represent a good model for the examination of the biological response of bTE scaffolds [14]. The results of the in vitro study are reported in Figs.…”
Section: In Vitro Cell-scaffold Interaction Studymentioning
confidence: 99%
“…The possibility to design and fabricate porous scaffolds with interconnected porosity and large pores, of the order of hundreds of microns, is of great importance in bTE to ensure the 3D migration and colonization of bone cells and the correct development of new bone tissue in vitro and in vivo [1,2,12,14]. In addition, the presence of a double scale pore size distribution and a nano-scale fibrous pore wall texture can improve fluids transport and cell-scaffold interactions in the entire construct [2,4,5].…”
Section: Morphology and Structural Properties Of Pla Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the papers about preparation of PCL/HA composite materials have been reported [13][14][15][16][17] . However, PCL/HA composite materials were mostly prepared by blend [18][19][20] , in the process of which HA were produced through hydrothermal synthesis 21 or sol-gel 22 , etc.…”
Section: Introductionmentioning
confidence: 99%